For the common good: the Church of England, Christian-Muslim relations and A Common Word - Amos, Clare (Islam and Christian-Muslim relations, 2009)
This paper seeks to explore some of the dynamics of Christian–Muslim relations today, particularly in England, and asks what might be the relationship between such dynamics and current Anglican theology, belief and practice. It explores the lecture of 7 February 2008 given by Archbishop Rowan Williams to the Royal Courts of Justice in London, and suggests that the Archbishop's remarks on this occasion are consonant with his understanding of Anglican ecclesiology. Finally the paper concludes by looking at the Archbishop's response to the document A Common Word and draws links between the Archbishop's interest in this document and his more domestic concerns.